The reality of mathematics teachers’ practice of Alternative evaluation methods s in distance education in light of the Corona pandemic - Al-Ghaeth, Amal Saleh (Journal of Educational and Psychological Sciences, 2021)
The aim of the research is to identify the reality of the practice of mathematics teachers for the middle stage in the city of Riyadh for electronic alternative evaluation methods in their distant education following the Corona pandemic. It also aimed to identify the effect of each variable (experience, training courses, qualification) on the average practice of teachers for them, and to Identify the differences between the average teachers’ practice of alternative evaluation methods in their distant education (after the Corona pandemic) than in urban education (before the Corona pandemic), and the search was used in that descriptive survey approach, and the search tool consisted of a questionnaire consisting of two parts, the first part is divided into Five axes were distributed to the research sample consisting of (101) middle school mathematics teachers in the city of Riyadh. The research concluded that the averages of female teachers ’practice of electronic alternative evaluation methods in their distance education were large for the tool as a whole and for all instrument axes, and the practice of peer evaluation occupied the highest rank, this was followed by the practice of self-evaluation, then evaluation by tests and electronic written assignments, then evaluation by electronic conceptual maps and finally evaluation using electronic achievement files. The research also reached There are differences in the average practice attributed to the variable (training courses), while there are no differences attributed to the two variables (experience and qualification), and it has also been found that there are differences in teachers ’practice of alternative evaluation methods in their education (attendance, distance education) in favor of distance education, and based on On the results, the research presented a set of recommendations and suggestions.